2001
DOI: 10.1063/1.1373433
|View full text |Cite
|
Sign up to set email alerts
|

Problematic p-benzyne: Orbital instabilities, biradical character, and broken symmetry

Abstract: Articles you may be interested inTheoretical prediction of nuclear magnetic shieldings and indirect spin-spin coupling constants in 1,1-, cis-, and trans-1,2-difluoroethylenes A benchmark theoretical study of the electronic ground state and of the singlet-triplet split of benzene and linear acenes J. Chem. Phys. 131, 224321 (2009); 10.1063/1.3270190 CCSD(T) study of the far-infrared spectrum of ethyl methyl etherThe equilibrium geometry, harmonic vibrational frequencies, and infrared transition intensities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
130
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(145 citation statements)
references
References 99 publications
12
130
0
3
Order By: Relevance
“…The C 1 AC 6 (C 3 AC 4 ) and C 1 AC 2 (C 5 AC 6 , C 2 AC 3 , and C 4 AC 5 ) bonds are predicted to be 1.438 and 1.366 Å , respectively, which are very close to the CASSCF(12,12)/ TZ2P values of Lindh and Persson [18] (the discrepancies being 0.004 Å for both) and similar to the results of the CCSD(T), MBPT, BPW91, and B3LYP calculations (see Table 1 and Ref. [48]) (the discrepancies being within 0.018 Å ). The 1TS s (connecting 1R s and 1P s ) has the C 2v symmetry.…”
Section: Bergman Cyclization Of 1rsupporting
confidence: 80%
“…The C 1 AC 6 (C 3 AC 4 ) and C 1 AC 2 (C 5 AC 6 , C 2 AC 3 , and C 4 AC 5 ) bonds are predicted to be 1.438 and 1.366 Å , respectively, which are very close to the CASSCF(12,12)/ TZ2P values of Lindh and Persson [18] (the discrepancies being 0.004 Å for both) and similar to the results of the CCSD(T), MBPT, BPW91, and B3LYP calculations (see Table 1 and Ref. [48]) (the discrepancies being within 0.018 Å ). The 1TS s (connecting 1R s and 1P s ) has the C 2v symmetry.…”
Section: Bergman Cyclization Of 1rsupporting
confidence: 80%
“…8.6, the quality of the results is further improved by single-point energy computations on the BLYP/6-31G* structures utilizing the Brückner-doubles coupled cluster approach including triple excitations perturbatively {BCCD(T), also called BD(T)} based on BS-UHF reference wavefunctions. In contrast, coupled-cluster computations with unmodified UHF molecular orbi- tals {CCSD(T)} give poor results although they often deal well with multireference problems when the effect of triple excitations is included; this is due to the fact that in some open-shell cases CCSD(T) overestimates the single cluster-amplitudes [97]. The use of Brückner orbitals, in which the singles contribution is zero due to orbital rotation, leads to a significant improvement [98].…”
Section: Cyclization Reactions Of Polyunsaturated Systemsmentioning
confidence: 88%
“…Intrinsic reaction coordinate [32] (IRC) computations were utilized to confirm the TSs. Single-point energies, using the same function but with a larger basis set (6-311+G*), were computed for all species; Brueckner doubles coupled-cluster energies [33,34] utilizing a cc-pVDZ basis set [BD(T)/cc-pVDZ] were additionally computed for comparison in some critical cases. The validity of the use of these computational schemes for these types of molecules has been demonstrated in our previous studies and were confirmed by other groups.…”
Section: Methodsmentioning
confidence: 99%